Multifunctional catalyst based on BaO/Pt/CeO2 for NO2-assisted soot abatement and NOx storage. (1st June 2015) - Castillo Marcano, S.J.; Bensaid, S.; Deorsola, F.A.; Russo, N.; Fino, D.
Highlights: A CeO2 /BaO/Pt catalyst was investigated for decreasing soot combustion temperature. NOx absorption capacity of BaO and soot oxidizing potential of NO2 were exploited. Catalyst formulation and preparation as well as reaction conditions were optimized. Onset and peak temperatures of soot combustion were decreased of about 30 °C. Abstract: In the present work the CeO2 /BaO/Pt system was selected in order to perform an NO2 -assisted soot oxidation. The aim of such catalytic system is to couple the catalytic functionality for soot abatement during DPF regeneration, namely CeO2, and an embedded lean NOx trap (LNT) functionality given by BaO, for NOx storage, whose oxidation over Pt to form adsorbed nitrates is facilitated by the presence of CeO2 itself. The impact of process parameters, such as the catalyst preparation and the reaction conditions, was analyzed. The activity towards soot oxidation revealed that a physical mixture of CeO2 and BaO allowed to obtain more performing catalysts than the co-synthesis route, the former reaching a peak temperature of soot oxidation equal to 475 °C, being 25 °C lower than the latter. The Pt addition to the two catalysts reduced their peak temperatures by around 30 °C in both cases. It is worth noticing that the onset temperature ( T 5% ) was considerably improved in presence of Pt only in the case of the catalyst prepared by co-synthesis (decreasing from 390 to 360 °C), still remaining much higher than the temperature level reached by the ones obtained by physical mixture (280 °C). As a result, in terms of soot conversion, CeO2 /Pt/BaO catalyst prepared by physical mixture can be considered the catalyst with the best behavior.